Sistemas precursores de cristais líquidos mucoadesivos para administração bucal de curcumina no tratamento do câncer bucal - Fonseca-Santos, Bruno [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Oral cancer is a highly incident disease in the world population and it can causes facial deformities and death. The choice treatment is costly and usually involves the administration of chemotherapy, which may have cytotoxic action also on healthy cells, which affects significantly the quality and survival of patients. Curcumin, naturally occurring compound isolated from the rhizomes of Curcuma longa, it has shown activity in the treatment of oral cancer, it acts on the nuclear factor kappa beta (NF-kB), which it mediates expression of genes that are involved in promoting tumors, angiogenesis and metastasis. However, its clinical use shows several challenges, mainly due to its physicochemical characteristics and low oral bioavailability. Thus, when incorporated in nanostructured systems precursors of liquid crystas (SPLC) added of a mucoadhesive polymer adjuvants, shows to be an interesting option to enable its use in the treatment of oral cancer, since these systems can protect the drug against degradation and to increase the residence time of the formulation in the oral environment, allowing a controlled release on an specific site of action. The aim of this study was to develop LCSP containing curcumin for oral administration in order to optimize the oral cancer treatment. The design of the systems was based on the construction of ternary phase diagrams by mixing PPG-5-CETETH-20, oleic acid and using aqueous dispersions added chitosan, poloxamer and a binary mixture of chitosan and poloxamer. However, the use of chitosan dispersion in the aqueous phase produced unstable systems and the stability can be improved with the addition of poloxamer with chitosan. The formulations were characterized by macroscopic appearance, polarized light microscopy (PLM), small angle X-ray scattering (SAXS), oscillatory rheology, texture analysis and analysis of in vitro mucoadhesion. The MLP show ...

O câncer bucal é uma doença altamente incidente na população mundial, podendo provocar deformidades faciais e morte. O tratamento de escolha envolve a administração de quimioterápicos, que podem apresentar ação citotóxica também sobre células saudáveis, diminuindo significativamente a qualidade e sobrevida dos pacientes. A curcumina, composto de ocorrência natural isolado dos rizomas da Curcuma longa, tem apresentado atividade no tratamento do câncer bucal, atuando sobre o fator nuclear kappa-beta (NF-kB), que medeia a expressão de genes que estão envolvidos na promoção de tumores, angiogênese e metástases. No entanto, seu uso clínico enfrenta muitos desafios devido às suas características físico-químicas e baixa biodisponibilidade oral. Assim, sua incorporação em sistemas nanoestruturados precursores de cristais líquidos (SPCL) acrescidos de adjuvantes poliméricos mucoadesivos para administração bucal demonstra ser uma opção interessante para viabilizar o seu uso, uma vez que estes sistemas conseguem proteger o fármaco da degradação e aumentar o tempo de permanência da formulação no ambiente bucal, possibilitando uma liberação controlada no local específico de ação. O objetivo deste trabalho foi desenvolver SPCL contendo curcumina para a administração bucal visando a otimização do tratamento câncer bucal. O delineamento dos sistemas se baseou na construção de diagramas ternários de fases pela mistura de PPG-5-CETETH-20, ácido oleico e utilizando fase aquosa adicionadas de dispersões de quitosana, poloxâmero e uma mistura binária de quitosana e poloxâmero. Entretanto, a utilização de dispersão de quitosana na fase aquosa gerou sistemas instáveis e essa estabilidade pôde ser melhorada com a adição de poloxâmero juntamente com a quitosana. As formulações foram caracterizadas macroscopicamente, por microscopia de luz polarizada, espalhamento de raio-x à baixo ângulo (SAXS),...
Keywords: Química farmacêutica; Cúrcuma; Neoplasias bucais; Fármacos; Farmacotécnica; Mouth neoplasms